Alpha Glukosidase Inhibitory Test and Total Phenolic Content of Ethanol Extract of Parkia Speciosa Plant - Fitrya Fitria; Annisa A.; Nikita S.; Ranna C. (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2019)
Parkia speciosa (Fabaceae), much grow in South Sumatera. The seed of P. speciosa used as traditional medicine for diabetes mellitus therapy. Another parts of P speciosa is suspected to have the same chemical compounds and potency as the seed. Based on phytochemical screening of leaf and rind of P speciosa have secondary metabolites as flavonoid, phenolic and terpenoid. This research aims to know effectiveness of alpha glucosidase inhibitory effect of ethanol extract of rind, leaf and seed of p. speciosa and its correlation to total phenolic content of the extracts. The inhibitory activity of the alpha glucosidase enzyme was measured at l 405 nm. The result showed that there was correlation between effectiveness of inhibitory and total phenolic content of the extract, that is the higher of the total phenolic content will caused the greater of enzymatic inhibition of extract. The IC50 of alpha glucosidase inhibitory effect of ethanol extract of rind, leaf and seed of P speciosa are 4,596 ppm, 54,341 ppm, dan 67,425 ppm and the total Phenolic content of the extract are 138,15 mgGAE/g, 59,25 mgGAE/g, dan 36,25 mgGAE/g respectively.